Pengaruh Teknologi terhadap Motivasi Belajar Siswa - Atikah Asna; Nur Amaliah; Puja Lestari; Zahwa Annadzira (Reflection : Islamic Education Journal, 2025)
Technology plays an important role in the education sector, especially in influencing students' learning motivation. This study aims to evaluate the influence of technology on students' learning motivation at various levels of education. The methods applied include literature review and observation of students who utilize technological devices in the learning process. The research findings show that the use of technology, such as learning applications, digital platforms, and interactive media, can increase students' interest and participation in learning activities. However, there are also challenges, such as the possibility of disruption due to the use of technology that is not managed properly. Therefore, careful management is needed in technology integration to ensure a positive impact on students' learning motivation.